Desperate measures : the life and music of Antonia Padoani Bembo - Fontijn, Claire Anne, 1960- (OUP E-Books., 2006)
One of the most fascinating figures of seventeenth-century music, composer and singer Antonia Padoani Bembo (c.1640 - c.1720) was active in both Venice and Paris. Her work provides a unique cross-cultural window into the rich musical cultures of these cities, yet owing to her clandestine existence in France, for almost three centuries Bembo's life was shrouded in mystery. In this first-ever biography, Clare Fontijn unveils the enthralling and surprising story of a remarkable woman who moved in the musical, literary, and artistic circles of these European cultural centers.